Nag Hammadi bibliography, 1995-2006 - Scholer, David M. (Nag Hammadi and Manichaean Studies, 2009)
This is the third volume of the immensely useful Nag Hammadi Bibliography , the first volume of which covered 1948-1969 and was the first publication in the Nag Hammadi Studies series. The second volume covered 1970-1994. This third volume provides a complete integration of Supplements II/1-II/8 to the Bibliography as published in Novum Testamentum 1998-2008, with additions and corrections. This latest update contains 3,063 entries, with the set of three volumes containing 11,580 entries. Nag Hammadi and Gnostic studies continue to be of critical importance for the study of ancient religions in the Graeco-Roman world and for the study of the world of early Christianity, and the present bibliography provides an indispensable reference tool for work in these fields.